Bursaphelenchus xylophilus, the pinewood nematode: its significance and a historical review - Tóth, Ágnes (Acta Biologica Szegediensis, 2011)
This paper reports on the biology, introduction, spread, damage and the control of Bursaphelenchus xylophilus (STEINER and BUHRER, 1934) NICKLE, 1970. Presenting a significant economic threat, the pinewood nematode is a unique quarantine status species of the genus Bursaphelenchus. The risk of its spread in European coniferous forests is especially high where the insect vectors are present. In Hungary, the pests B. mucronatus and B. vallesianusare present as well as its vector species Monochamus. Considering the health status of domestic planted pines, the severity of storm-damages, global warming, the increased volume of imported wooden packages and insect migration, the likelihood of B. xylophilus invading Hungary and finding favourable conditions keeps increasing.